Historical hegemony: fractured identity and mono-vocalization in Sadegh Hedayat's blind owl - Khalil Mahmoodi; Shanthini Pillai; Raihana , M.M (Universiti Kebangsaan Malaysia, 2012)
This article problematises the issue of history through the symbolic analysis of the woman in Sadegh Hedayat's Blind Owl as a metaphorical depiction of Iran. This article attempts to show how the various historical invasions led to the identity dilemma that produced people with instable, fractured identity and nameless individuals, like the narrator of the story. It tries to reveal the lament of the author for the psycho-historic social and political changes which changed the cultural discourses in his society, from what he considers as a pure one represented in the ethereal girl to an impure and polluted one objectified in the configuration of the whore, due to the different invasions and occupation of Iran, in the previous ages as the sources of the lack of identity in his age.